Tinjauan Pengelolaan Kas Kecil Pada PT Tirta Utama Abadi - Hekmatyar, Gema Pratama; Sari, Ervina Indri (Jurnal Aplikasi Bisnis Kesatuan, 2023)
The purpose of petty cash funds is to avoid uneconomic payments for relatively small amounts of expenditure so that petty cash can be coordinated and facilitate information about petty cash data that occurs in the company. For this reason, this study aims to determine the recording systems and procedures used by PT Tirta Utama Abadi The research method includes data collection techniques, namely direct observation and interviews with parties related to administrative functions. The data analysis used by the authors is descriptive analysis. From the results of this study indicate that PT Tirta Utama Abadi applies the fluctuation fund method, basically managing the petty cash is basically right. However, there are some errors according to the author in managing petty cash that is not in accordance with some opinions expressed by some accounting experts. Keywords: petty cash, cash management, fluctuation fund method